Aggregation‐Induced Emission and Circularly Polarized Luminescence Duality in Tetracationic Binaphthyl‐Based Cyclophanes. Issue 40 (22nd August 2022) - Garci, Amine; Abid, Seifallah; David, Arthur H. G.; Codesal, Marcos D.; Đorđević, Luka; Young, Ryan M.; Sai, Hiroaki; Le Bras, Laura; Perrier, Aurélie; Ovalle, Marco; Brown, Paige J.; Stern, Charlotte L.; et al.
Abstract: Here, we report an approach to the synthesis of highly charged enantiopure cyclophanes by the insertion of axially chiral enantiomeric binaphthyl fluorophores into the constitutions of pyridinium‐based macrocycles. Remarkably, these fluorescent tetracationic cyclophanes exhibit a significant AIE compared to their neutral optically active binaphthyl precursors. A combination of theoretical calculations and time‐resolved spectroscopy reveal that the AIE originates from limited torsional vibrations associated with the axes of chirality present in the chiral enantiomeric binaphthyl units and the fine‐tuning of their electronic landscape when incorporated within the cyclophane structure. Furthermore, these highly charged enantiopure cyclophanes display CPL responses both in solution and in the aggregated state. This unique duality of AIE and CPL in these tetracationic cyclophanes is destined to be of major importance in future development of photonic devices and bio‐applications. Abstract : Tetracationic enantiopure cyclophanes have been synthesized by the insertion of axially chiral enantiomeric binaphthyl fluorophores into the constitutions of pyridinium‐based macrocycles. These highly charged fluorescent cyclophanes exhibit aggregation‐induced emissions and display CPL responses both in solution and in the aggregated state.